Características clínicas e evolução da histoplasmose disseminada em pacientes com AIDS em hospital de referência do Ceará - Pontes, Licia Borges (2008)
Since the beginning of HIV epidemic in Ceará, disseminated histoplasmosis (DH) has been detected more often among aids patients. In order to know better clinical and laboratorial features, follow up and survival analysis of DH/AIDS co-infection, 134 medical records of inpatients with DH and 119 of patients without DH, from a reference hospital of Ceará, from 1999 to 2005 were analysed. The data was obtained from admission through two years later. Univariate and multivariate analisys of clinical and laboratory data was conduct with SPSS version 10.0 (SPSS Inc., Chicago, IL). Kaplan-Meier and Log-rank tests were used for survival analisys. Most (71,6% with DH and 79,8% without DH) of patients were men. The mean ± SD age of the patients was 35,5 ± 8,9 years and more than 90% of the patients had very low incomes in both groups. Twenty six patients (50%) with DH had a previous hospital admission for non tuberculosis respiratory infection compared to 13 (22.8%) patients without DH (p<0,05). Patients with DH had more fever (94%), daily (92,7%), higher than 38.5°C (78,6%), chills (41,1%), cough (77,1%), weight loss (89,9%), diarrhea (68,9%), vomiting (47%), enlarged liver (43,2%) and spleen (24,2%), skin lesions (14,9%) and jaundice (14,4%) (p<0.05). At hospital admission patients with DH had lower white cell count (4594,5±3873,6 versus 6030±3986cells/mm³), platelet count (121.737±101.054 versus 218.739±130.320cells/mm³) prothrombin time (56,6±17,6 versus 73,8±18,2%) and CD4 cell count (78,3±105,1 versus 112,3±114,5cells/mm³),as well as higher levels of serum creatinin (1,63±1,63 versus 1,16±1,19mg/dL), serum urea (60,9±59,6 versus 39,7±35,8mg/dL), LDH (4249±4248 versus 605±654UI/L), AST (245±289 versus 60±50UI/L), ALT (138±409 versus 43±40UI/L) and alkaline phosphatase (409±475 versus 205±257UI/L) (p<0,05). Hemoglobin8g/L and CD4 cell count100cells/mm³ were more common in DH pactients (p<0,05). Respiratory failure (RF) and sepsis were more common complications in DH patients (p<0,05). The diagnosis was maken mostly through direct microscopy (72,4%) and or through culture (49,3%) of biological material. Death during hospital stay was higher in DH patients (32,8% versus 25,2%) (p=0,213). At hospital admission, DH risk factors for death were: vomiting, dyspnea, respirophasic chest pain, RF, hemoglobin8g/L, serum urea≥40mg/dL and serum creatinine≥1,5mg/dL (p<0,05). Multivariate analysis showed hemoglobin8mg/dL, serum urea≥40 mg/dL at hospital admission as independent risk factors for death, with 10% significance level. DH relapsing was noted in 21.8% of cases during the study period and 64,7% of them died. Survival analysis showed significant higher mortality in DH group during the first month (p<0,05); afterwards the rate of death was similar in both groups. In conclusion, patients with DH had higher fever, more previous hospital admission for non tuberculosis pulmonary infection, more clinical complications compared to patients without DH. And had anemia (hemoglobin<8g/dL) and elevated serum urea (urea≥40mg/dL) as independent risk factors for death.